Meshless Improved Algorithm for Ion Flow Field in Large-Span AC-DC Parallel Lines - Zhang, Ruiyong; Cai, Chenlin; Xi, Haibo; Yao, Cheng (Recent Advances in Electrical & Electronic Engineering, 2023)
Background: The research in this paper aims to address the effect of large-span AC lines on ion currents in parallel DC lines. This paper proposes an algorithm for solving mixed ion flow fields based on meshless radial point interpolation, which can accurately solve the ion flow field of large-span AC-DC parallel lines. Methods: The shape function of the traditional meshless method is modified by polynomial radial point interpolation so that the shape function can satisfy the Kronecker-δ function property at the point where the boundary constraints are to be imposed so as to meet the requirements of directly applying the boundary constraints; Combined with the influencing factors of the AC line on the mixed ion flow field, the mixed ion flow field and the ion current density value was obtained. Results: Using the proposed algorithm, the relative error of ion current density can be reduced to 4.5%, and the relative error of ion flow field can be reduced to 24%. Conclusion: The simulation results are consistent with the measurement results, which proves the correctness and practicability of the mixed ion flow field solution algorithm based on meshless radial point interpolation.
Keywords: Kaptzov assumption